A great imitator in adult cardiology practice: congenitally corrected transposition of the great arteries. (22nd February 2017) - Agarwal, Anushree; Samad, Fatima; Kalvin, Lindsey; Bush, Michelle; Tajik, A. Jamil
Abstract: Introduction: Congenitally corrected transposition of the great arteries (ccTGA) is a rare congenital disease that frequently remains undiagnosed until adulthood, especially when there is an absence of other congenital anomalies. Adults with ccTGA may remain asymptomatic and their diagnosis could be missed on initial evaluation, or it could be diagnosed incidentally as an evaluation of murmur. We aim to report the different presentations of ccTGA in eight adult patients and review the key features required to suspect the diagnosis during an initial visit. Cases: We present some illustrative cases of ccTGA patients who had diverse presentations ranging from being completely asymptomatic to presenting with an acquired heart disease resulting in sudden cardiac arrest. Overall, most of these patients had isolated ccTGA with no other significant associated cardiac anomalies and were either undiagnosed or lost to follow‐up until adulthood. These case illustrations represent the challenges confronted in adult practices when patients with unrecognized ccTGA present during an initial visit. Conclusions: Congenitally corrected transposition of the great arteries poses a challenge in the adult cardiology practice because of its diverse clinical presentation. It is crucial that internists, cardiologists, and sonographers maintain a high degree of suspicion after meticulous physical examination for the early recognition of ccTGA, and thus avoid associated morbidities. Through some case examples, we provide clues to the key diagnostic features that could help them to be vigilant in making a diagnosis.